PERAN MAJELIS GHUNG GARUDA DALAM MENGEMBANGKAN PEMAHAMAN DAN KECINTAAN SANTRI TERHADAP PRAKTIK BERSHOLAWAT DI YAYASAN PONDOK PESANTREN NURUL JADID ULUBATU DESA TANJUNG PADEMAWU PAMEKASAN - Syaiful Anam; Muliatul Maghfirah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of spiritual development of Islamic boarding school students through religious activities that can foster a love of shalawat as part of strengthening religious character. The Ghung Garuda Assembly exists as a forum for development that integrates spiritual values, character education, Islamic art, and social togetherness in shalawat activities. This study examines the strategic role of the Ghung Garuda Assembly in increasing the involvement of Islamic boarding school students in the practice of shalawat at the Nurul Jadid Islamic Boarding School Foundation in Lubabatu and analyzes its impact on changes in attitudes and mental conditions of students. This study uses a qualitative approach with a field research type. Data were obtained through observation, in-depth interviews, and documentation of caretakers, assembly administrators, and active students involved in activities. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, while data validity was tested through triangulation of sources and techniques.